COPUS, PORTAAL, or DART? Classroom Observation Tool Comparison From the Instructor User’s Perspective - Asgari, Mitra; Miles, Asha M.; Lisboa, Maria Sol; Sarvary, Mark A. (Frontiers in Education, 2021)
Classroom observation tools are used to evaluate teaching and learning activities, and to provide constructive feedback to instructors. To help instructors with selecting a suitable tool based on their needs and available resources, in this study a group of observers assessed lectures of an introductory biology course using three, broadly cited classroom assessment tools in the STEM field: the Classroom Observation Protocol for Undergraduate STEM (COPUS); the Practical Observation Rubric to Assess Active Learning (PORTAAL); and the Decibel Analysis for Research in Teaching (DART). From a user’s perspective, we evaluated 1) the type and extent of information each tool provides, and 2) the time investment and difficulty of working with each tool. The assessment result of each tool was compared, with a list of expected outcomes generated by surveying a group of college instructors and with the result of a self-teaching assessment tool, the Teaching Practices Inventory. Our findings showed that each tool provided valuable assessment with a broad range of investment and outcomes: PORTAAL offered the most detailed information on the quality of teaching practices and students’ engagement, but it demanded the greatest time investment. DART provided a basic estimation of active learning with the least effort. Regarding both the details of the outcome and the invested effort, COPUS was found to be between what PORTAAL, and DART provided and required. This comparative study can help instructors select a tool that suits their needs and available resources for a better assessment of their classroom teaching and learning